Efektivitas dan Efisiensi Penggunaan Sistem Syncore dalam Menyajikan Laporan Keuangan (Studi Kasus di Puskesmas Kalangsari) - Dwi Atika Santya Putri; Dwiyani Sudaryanti; Hariri Hariri (Universitas Islam Malang, 2023)
This study was conducted to analyze the effectiveness and efficiency of the Syncore system in presenting financial reports. The research method used in this study is a qualitative method with the data source used being primary data and data collection techniques through joint interviews with direct users of the Syncore system, namely the Treasurer at the Kalangsari Health Center, Karawang Regency. The analytical method in this study uses descriptive and triangulation methods in order to achieve the validity of the data from the interview results.Based on the overall results of interviews with the Treasurer, Head of administration, and Head of the Kalangsari Health Center, as well as one of the employees at PT Syncore Indonesia regarding indicators for measuring the effectiveness and efficiency of a system against the Syncore system, the results obtained from this study describe that the indicators for measuring both effectiveness and efficiency are in accordance with user needs. Therefore, it was concluded that the use of the Syncore system in presenting financial reports has been effective and efficient at the Kalangsari Health Center.Keywords: Effectiveness, efficiency, Syncore system, financial reports, public health centers BLUD